Broken promises of the First Republic: The connection between social and equal rights of minorities in Carinthia, Austria - Clar, Maria (Momentum Quarterly, 2021)
After the First World War, states disintegrated in Europe, and in some regions, questions arose about the demarcation of borders. This was also the case in the then mainly Slovenian-speaking part of Carinthia in southern Austria. In October 1920, a vote was taken on state affiliation. The decisive factor was the political system of the so-named First Republic and the associated promises of social and equal rights as well as economic factors. A hundred years later, it becomes clear, that not all promises have been kept. It encourages reflection on how the rights of minorities can be incorporated into democracies. The present article, with a focus on the minutes of the provisional Carinthian federal-state assembly and the Carinthian provincial government, examines how participation, social rights, and the relationship between minority and majority, have found their way into a momentous political decision. It becomes clear how social issues and the possibility of language retention are an intertwined part of the regional history of Carinthia. Subsequently, the dependence of minority rights on the willingness of hegemonic groups to implement them can be discussed.